Integration of social environmental factors in the valuation of corporate fixed income securities - Mattos, Marcos Costa; Lemme, Celso Funcia (Revista de Administração da UFSM, 2020)
This study presents a diagnosis of the current practices and a proposal of a roadmap for integrating social environmental variables in corporate fixed income securities valuation. The roadmap does not make a distinction between the different forms that the securities can take on and was developed by identifying the best integration practices adopted by market players. The sample was formed by 67 agents from the corporate fixed income securities market obtained by criteria of engagement in sustainable finance and relevance in the fixed income securities market. The diagnosis indicated a weak consideration of social environmental variables in the valuation of fixed income securities with little difference among the practices of the domestic and foreign financial institutions with credit rating being the main approach used. The roadmap proposed presents basic considerations of risks and opportunities following the path of analysis the sector and corporate social environmental factors accompanied by adjusting contractual rate spreads. The specific contributions expected from the study are to improve the financial strategy of companies, reach greater efficiency in investor portfolio management, and provide guidance that is more adequate by the regulators and formulators of public policies.